REVIEW PENGENDALIAN LIMBAH PADAT SERTA BAHAN BERBAHAYA (B3) DI RUMAH SAKIT - Muhammad, Muhammad; Annisa Zahra; Suciati Nurrani; Halimi, Halimi; Nor Latifah; Yulianita Pratiwi Indah Lestari (Jurnal Cakrawala Ilmiah, 2024)
Health waste is waste generated from health activities it hospitals. Hospital operations generate a variety of waste byproducts, solid waste that contain hazardous and poisonous bacteria. Operational activities and B3-containing service facilities generate hazardous and toxic waste. The purpose of this study is to learn more about and gain an understanding of how hospitals handle hazardous and toxic chemicals (B3) and solid waste. The purpose of this study is to learn more about and understand how hospitals handle hazardous and toxic materials (B3) as well as solid waste. A review of the literature sourced from reputable pharmaceutical publications, PubMed, Google Scholar, and other literature search results is the methodology employed. The analysis chosen articles was of the hospital's solid and (B3) waste management system. From the literature search, 7 journals out of 1,910 articles were found that matched the criteria with the search string 2015 to 2024. The study's findings demonstrated the necessity of trash sorting for the efficient management of hazardous chemicals (B3) and solid waste in hospitals. collection and destruction. Techniques such as incineration of medical waste and proper segregation of non-medical waste are important to prevent negative impacts on health and the environment.